Non-binding norms in international humanitarian law efficacy, legitimacy, and legality - Crawford, Emily (Writer on international law) (Oxford, United Kingdom Oxford University Press, 2021)
This monograph examines and analyses the phenomenon of non-binding instruments (also known as 'soft law') in the law of armed conflict, or international humanitarian law. It covers the benefits and drawbacks for States and non-States actors as well as their effectiveness and development in the context of armed conflict.
Includes bibliographical references (pages 257-275) and index.
Keywords: Humanitarian law. -- Electronic books; Natural law; Social norms; Humanitarian law; Natural law; Social norms